Evidences for flow‐assisted interfacial reaction in coextruded PA6/PP/PA6 films. (27th February 2018) - Kiparissoff‐Bondil, H.; Devisme, S.; Rauline, D.; Chopinez, F.; Restagno, F.; Léger, L.
Abstract : We present an investigation of the progressive building of copolymer layers formed by chemical reaction at interfaces in multilayer coextruded polymer films. Analyzing the surface density of copolymers in the final films, we show that the interface always remains under‐saturated in copolymers, even for coextrusion parameters such that the time open to the interfacial chemical reaction is well above the time necessary to reach saturation without flow. Based on a numerical analysis of the flow all along the coextrusion line, we show that this under‐saturation of the interface, which may strongly affect the final adhesion between the different polymers, results from a competition between the interfacial chemical reaction and the dilution of yet formed copolymers in all the zones of the coextrusion line where surface of interface is increased, due to convergent, divergent or elongational flow. We also show that the coupling between flow and reaction kinetics needs be taken into account to control the final surface density of copolymers and precisely optimize the interfacial properties, through an optimization of the coextrusion parameters POLYM. ENG. SCI., 59:E44–E50, 2019. © 2018 Society of Plastics Engineers